Compact Model for Nano-Wire Tunnel Field-Effect Transistor. (27th March 2015) - Sato, Shingo; Omura, Yasuhisa; Mallik, Abhijit
Abstract : This paper presents a compact model of the Nano-Wire Tunnel Field-Effect Transistor (NW-TFET). We analyze the validity of the previous-reported transmission probability and our model using an analytical potential model with a depletion approximation. We clarify the difference between the models by using the ratio of channel length to natural length to characterize the NW-TFET. By considering the offset of the gate voltage, the tunnel probability of our model can reproduce the numerically derived one for any channel length near the on-state. Finally, we present a compact model of the drain current.